Fontes artificiais de luz: aferição da emissão de radiação ultravioleta como base para sua correta utilização no interior de monumentos tombados e museus - Leonardo Barreto de Oliveira (2003)
Several lamps available in the Brazilian market have been tested for their level of emitted ultraviolet radiation. The information obtained after the measurements are fundamental for the definition of more appropriate technical specifications for interior lighting projects in buildings holding collections or artistic objects, as well as those buildings for storage and exhibition of cultural properties. The ultraviolet radiation levels must be controlled and monitored in order to not be superior to the recommended values. For the experiments weve used a UV monitor with three different sensors in the regions of 220-300 nm; 310-400 nm e 360-480nm. Havingnot found in the literature a stablished methodology for the measurements, the present work stablished parameters for the experimental work, with basis on the equipment used for the data gathering, as well as the national and international standards which showed to be more closer to the theme and the actual use of the lamps. The results of the measurements are presented in several tables containing the light sources with their respective values of emitted UV light, which will serve as reference for the specification of lamps. It became obvious the need for further development of research in this area of knowledge, mainly in relation to standardization for measurements, calibration sources and the units for the data acquired.